Quality of life is a primary end-point in clinical settings - José Luís Pais Ribeiro (2004)
The objective of this review is to present and discuss the quality of life (QOL) construct, more specifically the QOL in the field of health and disease also designated as health-related quality of life (HRQOL). QOL is an everyday language concept with a relatively short history in the health field. It became a principal, end rights the development of patients point in health care as a consequence of movements. It is important for clinical, economic and political decisions. There is no a gold standard way to measure QOL and the existence of a huge number of measures makes it difficult to discuss QOL. This means that many and related QOL concepts times we are using the same expression "QOL" but we are not talking about the same the good construct and the thing. So we submit that it is important-to keep looking for good measure. The reason why we decide to evaluate QOL influences the measures we choose. In general, QOL measures are based on questionnaires that must be short and-easy to answer. The interest in these kind of soft measures (in opposition to the traditional. hard physiologicatly or biochemically oriented measures) is growing fast.